2012
DOI: 10.1158/1538-7445.am2012-2692
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2692: An ongoing Phase II trial of an adenovirus/PSA vaccine for prostate cancer

Abstract: Introduction and Objectives: Our Phase I adenovirus/PSA vaccine trial has proved that this vaccine is safe. We are conducting a Phase II clinical trial with two separate protocols for patients with recurrent or hormone refractory prostate cancer assessing toxicity, immune responses, and changes in PSA levels. Methods: In Protocol #1 men with recurrent prostate cancer following definitive initial treatment for their disease were placed in one of two arms: Arm A; men receive the vaccine alone at days 0, 30, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In response to vaccination, 34% of patients generated anti-PSA antibodies, 68% developed anti-PSA T cell responses, 48% had an increased PSA doubling time, and 55% survived longer than predicted (53). An ongoing Phase II clinical trial (NCT00583024) investigating adenovirus/PSA responses in men with hormone refractory prostate cancer showed anti-PSA T cell responses were present in 100% of patients with recurrent disease and 67% in patients with hormone refractory disease (54). A newly recruiting phase I clinical trial will examine how mCRPC patients will respond to adenoviral PSA (ETBX-071), MUC1 (ETBX-061), and ETBX-051 (brachyury) vaccines (NCT03481816).…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…In response to vaccination, 34% of patients generated anti-PSA antibodies, 68% developed anti-PSA T cell responses, 48% had an increased PSA doubling time, and 55% survived longer than predicted (53). An ongoing Phase II clinical trial (NCT00583024) investigating adenovirus/PSA responses in men with hormone refractory prostate cancer showed anti-PSA T cell responses were present in 100% of patients with recurrent disease and 67% in patients with hormone refractory disease (54). A newly recruiting phase I clinical trial will examine how mCRPC patients will respond to adenoviral PSA (ETBX-071), MUC1 (ETBX-061), and ETBX-051 (brachyury) vaccines (NCT03481816).…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…An early stage analysis of an ongoing Phase II study with Ad 5 -PSA vaccine, using 2 different protocols for patients with recurrent or hormone-refractory prostate cancer, showed the induction of anti-PSA T-cell responses in a high percentage of vaccinated patients. In addition, there was an increase in PSA doubling time in about 64% of the patients [26]. These studies provide supportive evidence for the potential use of a second generation Ad 5 -PSA+PSCA bivalent vaccine for prostate cancer in clinical testing.…”
Section: Discussionmentioning
confidence: 67%
“…In Protocol 2, men with hormone refractory disease received Ad5-PSA alone using the same three injection schedules, however Ad5-PSA was suspended in the gelfoam matrix. All of the patients in protocol 1 and 67 % of the patients in protocol 2 induced significant anti-PSA T cell responses; 64 % of the patients showed an increase in PSA doubling time [65].…”
Section: Ad5-psamentioning
confidence: 98%
“…A phase I trial of Ad5-PSA with or without gelfoam matrix in patients with PC, was shown to be safe (the primary endpoint of the trial), and anti-PSA T cell responses were induced in the majority of patients, however an increase rate rise in PSA (PSA doubling time) was noted in 50 % of patients [64]. A Phase II clinical trial of two separate protocols for patients with recurrent or hormone refractory PC were assessed for toxicity, immune responses, and changes in PSA levels [65]. In Protocol 1, men with recurrent PC following definitive initial treatment for their disease, either received Ad5-PSA alone on days 0, 30, 60, or received Ad5-PSA 14 days after the initiation of androgen deprivation therapy, 3 times, 30 days apart.…”
Section: Ad5-psamentioning
confidence: 99%